Tinjauan Sistem Informasi Akuntansi UMKM Berbasis Cloud - Rahadian Prilahardo (BIP's JURNAL BISNIS PERSPEKTIF, 2016)
The purpose of this study is to identify considerations of acquiring Cloud based Accounting Information System as Software as a Service (SaaS) towards small to medium businesses which has evolve alongside information technology revolution by comprehensively review basic concept of cloud computing and flexibility and agility values added by cloud computing onto conventional Accounting Information System thus may change the decision making process for small to medium business owners and management. This study provides comprehensive review of Cloud-based Accounting Information System and Non-cloud for small and medium business.